TLR-9 Plays a Role in Mycobacterium leprae-Induced Innate Immune Activation of A549 Alveolar Epithelial Cells - Dias, André Alves; Silva, Carlos Adriano de Matos e; Silva, Camila Oliveira da; Linhares, Natasha Ribeiro Cardoso; Santos, João Pedro Sousa; Vivarini, Aislan de Carvalho; Marques, Maria Ângela de Mello; Rosa, Patrícia Sammarco; Lopes, Ulisses Gazos; Berrêdo-Pinho, Márcia; Pessolani, Maria Cristina Vidal (Frontiers in Immunology, 2021)
The respiratory tract is considered the main port of entry of Mycobacterium leprae, the causative agent of leprosy. However, the great majority of individuals exposed to the leprosy bacillus will never manifest the disease due to their capacity to develop protective immunity. Besides acting as a physical barrier, airway epithelium cells are recognized as key players by initiating a local innate immune response that orchestrates subsequent adaptive immunity to control airborne infections. However, to date, studies exploring the interaction of M. leprae with the respiratory epithelium have been scarce. In this work, the capacity of M. leprae to immune activate human alveolar epithelial cells was investigated, demonstrating that M. leprae-infected A549 cells secrete significantly increased IL-8 that is dependent on NF-κB activation. M. leprae was also able to induce IL-8 production in human primary nasal epithelial cells. M. leprae-treated A549 cells also showed higher expression levels of human β-defensin-2 (hβD-2), MCP-1, MHC-II and the co-stimulatory molecule CD80. Furthermore, the TLR-9 antagonist inhibited both the secretion of IL-8 and NF-κB activation in response to M. leprae, indicating that bacterial DNA sensing by this Toll-like receptor constitutes an important innate immune pathway activated by the pathogen. Finally, evidence is presented suggesting that extracellular DNA molecules anchored to Hlp, a histone-like protein present on the M. leprae surface, constitute major TLR-9 ligands triggering this pathway. The ability of M. leprae to immune activate respiratory epithelial cells herein demonstrated may represent a very early event during infection that could possibly be essential to the generation of a protective response.